2020
DOI: 10.3390/rs12233929
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Driving Forces and Environmental Effects of Urban Expansion by Mapping the Speed and Acceleration of Built-Up Areas in China between 1978 and 2017

Abstract: Abundant data sets produced from long-term series of high-resolution remote sensing data have made it possible to explore urban issues across different spatiotemporal scales. Based on a 40-year impervious area data set released by Tsinghua University, a method was developed to map the speed and acceleration of urban built-up areas. With the mapping results of the two indices, we characterised the spatiotemporal dynamics of built-up area expansion and captured different types of expansion. Combined with socioec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“…This is in line with other studies that reported the dominance of anthropogenic activities in driving LULC change [89][90][91]. Anthropogenic activities are often rapid and tend to affect large tracts of land when compared to natural processes [5,[92][93][94]. This study is novel in the sense that it yielded spatially explicit information on the extent of LULC change spread, including detecting likely pathways of the spread for the different categories investigated.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This is in line with other studies that reported the dominance of anthropogenic activities in driving LULC change [89][90][91]. Anthropogenic activities are often rapid and tend to affect large tracts of land when compared to natural processes [5,[92][93][94]. This study is novel in the sense that it yielded spatially explicit information on the extent of LULC change spread, including detecting likely pathways of the spread for the different categories investigated.…”
Section: Discussionsupporting
confidence: 88%
“…According to Seybold et al [3] and Martin et al [4], LULC changes affect climate processes, biogeochemical cycles, nutrient loads, and water resources. Tracking the spatial, temporal, and likely pathways of LULC changes is crucial for landscape management and ecosystem services assessments [5][6][7]. Owing to their complexity and role as key livelihood support systems for over 60% of the world's population, interest in how LULC changes within transboundary basins (TDBs) and its effect on natural resources distribution is of high priority [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…If the other parameters are fixed, only the contribution of land and capital to the economy is considered, capital could stimulate the economy, and land and capital could be replaced by technology. Thus, average fixed-asset investment was selected as an indicator to evaluate land-use intensity [ 30 ].…”
Section: Framework Analyzing the Driving Factors Of Urban Land Expans...mentioning
confidence: 99%
“…There are various metrics applied to quantify the degree of urban expansion, such as the expansion area, speed, and acceleration of built-up [3]. In this study, we defined the urban spatial-expansion index as the percent of built-up area (PB), which equals the area of urban landscape divided by the total area of study unit.…”
Section: Urban Spatial-expansion Indexmentioning
confidence: 99%
“…Urban spatial expansion is one of the most dramatic types of land use and land cover change (LUCC) and exerts irreversible human impacts on the global biosphere [1,2]. Urbanization due to urban population growth and economic development has intensified expansion of the built environment [3], resulting in the conversion of a large amount of natural landscapes into non-vegetated artificial landscapes such as roads, buildings, and other infrastructures [4]. Although the global built-up area was only 0.65% in 2010 [5], LUCC in urban areas has become one of the primary drivers of habitat loss and species extinction all around the world [6].…”
Section: Introductionmentioning
confidence: 99%